ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DAN PROFESIONALISME GURU SERTA DAMPAKNYA TERHADAP KINERJA GURU - Zulher Zulher; Syahrial Syahrial (STMIK Pringsewu, 2023)
Teacher performance is closely related to increasing teacher empowerment where teachers must be able to independently criticize the curriculum, be able to manage their classes and teaching materials and be able to improve their teaching methods efficiently. Many factors can affect teacher performance including the leadership of the principal and teacher professionalism. For this reason, the purpose of this study was to identify and analyze the influence of teacher leadership and professionalism on teacher performance both personally and simultaneously. This research was conducted at SDN 001 Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency. The research was conducted for 3 (months) months starting in June 2022 until August 2022. The research data consisted of primary data and secondary data obtained using questionnaires, observations and research files. The population of this study were all teachers at SDN 001 Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency, totaling 32 people and all of them were used as a census. The data analysis tool used is multiple linear regression and hypothesis testing is done by t test and F test using an alpha of 5%. Based on the results of the study, it was concluded that the principal's leadership had a partially significant effect on teacher performance. This shows that the better the leadership attitude shown by the school principal, the more positive impact it will have on improving teacher performance. The result of testing the hypothesis is that teacher professionalism has a partially significant effect on teacher performance. The results of testing the third hypothesis show that principal leadership and teacher professionalism have a significant simultaneous effect on teacher performance at SDN 001 Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency.